Working through whiteness : international perspectives - Levine-Rasky, Cynthia (SUNY series, interruptions--border testimony(ies) and critical discourse/s., 2002)
"What is whiteness? What is gained by claiming it as a critical perspective in antiracism work? How do whiteness studies both redeem and assert the white subject? Working through Whiteness explores these questions through essays by Canadian, American, British, and Australian scholars, reflecting the broad array of academic inquiry into whiteness in the areas of law, ethics, education, feminism, politics, psychology, sociology, criminology, and social geography. Rarely has knowledge of whiteness as the practice of social domination been drawn from this far and wide. By embracing the leading edge in critical theory, this book is a crucial addition to the growing literature on whiteness."--Jacket